Pengaruh Jarak Kerapatan Penghalang Spiral Terhadap Unjuk Kerja Kolektor Surya Tipe Plat Datar - Dody Prasetiyo Guritno; ikhwanul Qiram; Dewi Sartika (Virtual of Mechanical Engineering Article, 2018)
The solar collector is a device that serves to collect solar radiation and convert it into useful energy of calories. Solar water heater collectors are heat exchangers that convert solar radiation energy into thermal energy in water. This research is done by modifying the existing pipe in the solar collector, wherein the pipe is given a barrier in the form of a spiral stainless wire with the difference of size that is 0.5 cm, 1 cm, and 2 cm. This study was conducted for nine days. The result of this research proved that the distance of the spiral barrier in solar collector has an effect on efficiency, the smaller spiral barrier distance makes the collector efficiency increases. It’s caused by the flow of water fluid in the pipe collided with the spiral shaft and formed following the spiral groove so as to increase the water temperature difference higher, with the higher water temperature difference then the value of solar energy useful solar collector increases. The increased heat energy is useful to the efficiency of solar collectors, where the efficiency of collectors will increase as well. The discharge flow also affects the collector efficiency, the more greater the rate of water flow, the collector's efficiency will decrease. It’s because the residence time of water in the heating pipe is shorter and the mass flow rate is greater. Furthermore, the value of solar energy useful solar collector is getting down so that collector efficiency is getting down anyway. The maximum collector efficiency occurs at a 0.5 cm spiral barrier distance with 1 liter / minute water discharge of 24.72%, while minimum efficiency occurs at 2 cm spiral barrier distance with water discharge of 3 liters/ minute that is 11.75%.